Conocimiento y su relación con la relevancia de la contabilidad ambiental en estudiantes del último nivel de contabilidad de la Universidad Nacional de la Amazonia Peruana año 2024 - Flores Gutierrez, Elvira Noemi (2025)
Environmental accounting is a branch of accounting that is gaining importance due to the emerging environmental concerns of humanity. However, its dissemination and expansion are affected by the lack of inclusion in the university curriculum for accounting students and how this fact affects its relevance. The objective of the research was to analyze the level of knowledge about environmental accounting and the relationship with its relevance in accounting students at the National University of the Peruvian Amazon in 2024, with a quantitative, descriptive and non-experimental approach, applying a 20-question questionnaire to a population of 82 students. The research reveals a positive and significant correlation between the level of knowledge and the perception of relevance of environmental accounting, indicating that students with greater knowledge tend to value it more in their training. Only 41% of students have adequate knowledge in this area, while there is a lack of practical training on specific standards such as IFRS S1 and S2. Although 78% of respondents perceive environmental accounting as relevant, its presence in the curriculum is limited. The use of environmental accounting as a tool for sustainability is the most valued aspect, with 88% acceptance. However, only 22% of students have had experience in preparing financial statements with an environmental focus, which reflects a low practical application.